DECISION SUPPORT SYSTEM FOR ADMISSION OF CLASS X STUDENTS WITH THE WEB-BASED SAW METHOD AND SMS GATEWAY AT SMA NEGERI 1 WANADADI - Akhmad Pujiyanto; Moh Muthohir (Journal of Engineering, Electrical and Informatics, 2021)
Education is a necessity that every human being must have, and is expected to provide useful knowledge in the future. Education itself consists of formal education and non-formal education, formal education is structured and tiered, while non-formal education is an educational path that is carried out in a structured and tiered manner like the pursuit of package A. With the development of education, the need for information technology to support the provision of information quickly. The development of web-based technology is an information space where useful resources are identified by global identifiers. With the development of technology, a web-based application for decision support for class X student admissions and sms gateway was designed. Admission and selection of majors at SMA Negeri 1 Wanadadi online is expected to make it easier for prospective students to register and get information from the results of class X student admissions.